Undertaking field research. (January 2017) - Soukup, Tayana; Lamb, Benjamin W; Sevdalis, Nick; Green, James SA
Ethnography, also known as field research, is a social science approach to studying people and groups in their natural setting. The methodology employed is qualitative, including observations and interviews. Analysis of documents, meta-ethnography and further mixed methods to obtain and analyse data collected from the field can be used to complement this. There is a general lack of field research within the healthcare setting, although it is particularly useful for understanding complex systems, and has been employed successfully in recent years to study cultures, safety and to improve quality.